Driving and dementia: What factors influence how physicians address the issue? Data from the Swedish Dementia Registry (SveDem) - Dorota Religa (402059) (2015)
Introduction In Sweden, physicians are required to report dementia patients who are unfit to drive to the Swedish Transport Agency (STA). However, physicians may refrain from reporting if there is reason to believe that the patient will cease to drive as part of an agreement. Aims To investigate to what extent physicians address driving and dementia, and whether there is a difference in how the issue is addressed depending on patient-related factors. Material and Methods: Data on 13852 newly diagnosed dementia patients, who held a driver's license, was obtained from the Swedish Dementia Registry. Associations between patient-related factors and being reported, or an agreement being reached, were examined in binary logistic regression. Results Physicians had not taken any action in 17% of cases. Male gender (OR 2.97, p<0.001) and living alone was associated with an increased likelihood of being reported to the STA. When compared to Alzheimer's disease (AD), Frontotemporal dementia (FTD) displayed a similar association (OR 2.38, p<0.001), while the inverse was observed in dementia with Lewy body (DLB) (OR 0.58, p=0.025). Conclusions Physicians, collectively, omit to address the issue of diving and dementia in almost 20% of dementia patients, and are thus noncompliant with national law and regulations. Furthermore, a difference in practice was observed in patients with DLB and FTD, but more evidence is needed in order to determine what the practical implications are. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.42